Employment status and women's fertility: Do working women have fewer children? - Yulmardi, Yulmardi; Erfit, Erfit; Dios Nugraha, Putra (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study aims to analyze the differences in fertility between employed and unemployed women in Jambi City and identify the socio-economic factors influencing the number of children they have. The study applies Propensity Score Matching (PSM) to ensure a fairer comparison between the two groups and Inverse Probability Weighting (IPW) to control for other variables that may affect the relationship between employment status and fertility. The results of the analysis indicate that the average number of children is higher among unemployed women than among employed women. However, after applying IPW weighting, employment status no longer has a significant effect on the number of children. Instead, economic factors, particularly household income, play a more significant role in determining fertility. Additionally, women’s age contributes to fertility differences, with older women tending to have fewer children. Meanwhile, education level and age at first marriage do not show a significant effect after weighting.